A low-molecular-weight fluorescent sensor with Zn2+ dependent bathochromic shift of emission wavelength and its imaging in living cells. (February 2015) - Hagimori, Masayori; Mizuyama, Naoko; Tominaga, Yoshinori; Mukai, Takahiro; Saji, Hideo
Abstract: Novel, low-molecular-weight fluorescent sensors based on a pyridine–pyridone core structure, which functions as both the chelating part moiety for Zn 2+ and as the fluorophore, were investigated. The length of the methylene spacer between the phenyl ring and the 3-position of the pyridone ring greatly influenced the emission wavelength and intensity upon Zn 2+ binding. 5-Benzyl-4-(methylsulfanyl)-[2, 2′-bipyridin]-6(1 H )-one (2 ) (MW = 308) with a methylene spacer of n  = 1 showed good water solubility, a 30 nm bathochromic shift in its emission wavelength and an 18-fold fluorescence enhancement in response to Zn 2+ . In addition, fluorescence microscopy imaging showed that 2 could be used to detect Zn 2+ in living cells. Graphical abstract: Highlights: Pyridine–pyridone fluorescent sensors exhibited a bathochromic shift with Zn 2+ . The length of the methylene spacer influenced the fluorescent properties with Zn 2+ . Compound 2 could be applied in the detection of Zn 2+ within living cells.